ANALISIS PERKUATAN STRUKTUR JEMBATAN DALAM KONDISI DI BAWAH BEBAN MUATAN MELEBIHI KAPASITAS - Anggraeni, Indri (Direktorat Bina Teknik Jalan dan Jembatan, 2025)
Bridges are sometimes crossed by vehicles with loads exceeding their capacity. For example, the Ijen Crater Bridge 2 in East Java will be crossed by heavy vehicles loaded with 109 tons of generators, while the bridge load capacity is only 56 tons. Therefore, a comprehensive condition evaluation and appropriate reinforcement recommendations are needed. The research methods used include visual inspection, non-destructive testing (NDT), and structural modelling using SAP2000 software. Through visual inspection, general damage to the bridge was identified. NDT was used to obtain quantitative data on the material's condition. The results of both methods are input into structural modelling to analyze bridge behaviour under operational loads. The analysis results indicate that the maximum capacity ratio of the structure is 0.796. This value is below 1, which means that the structural capacity has met the requirements after reinforcement. The maximum deflection value of the structure stiffness is 3.582 mm or less than the allowable deflection of 15 mm, which means it has met the criteria. The moment analysis after reinforcement produces a Mu value of 121.387 kNm, or still greater than the Mn value of 69.6 kNm. Therefore, it is recommended to strengthen the concrete floor slab structure according to the results, including the use of Carbon Fibre Reinforced Polymer. Steel portals are installed in the middle of the bridge span, and shallow foundations are built in the river flow area. This study demonstrates that bridge reinforcement necessitates a comprehensive analysis and solutions to ensure the safety of the bridge structure is maintained. Kata Kunci: jembatan kawah ijen, perkuatan jembatan, portal baja, muatan khusus, kapasitas struktur. Keywords: ijen crater bridge, bridge reinforcement, steel portal, special load, structure capacity